Vertical angles are formed when two lines intersect, and two angles that are on opposite sides of both lines.
The angles on the west side and the east side form two vertically opposite angles (commonly called vertical angles, but much less descriptive).
It is because the west angle is to the left of both lines, and the east angle is to the right of both lines.
Vertically opposite angles (vertical angles) are congruent. Therefore we can form the equation
110 = 5x
Divide both sides by 5 to get
110/5=22 = 5x/5 = x
or
x=22 degrees.
Step-by-step explanation:
19.50 i got that if i got it wrong mb
Answer:
351
Step-by-step explanation:
Complete question :
Vanilla= 36
Chocolate=21
Strawberry=24
Chocolate Chip=39
SOLUTION:
39 chocolate chip to 200 students = x chocolate chip to 1800 students
39/200 = x / 1800
Solving for 'x'
(200)(x) = (39)(1800)
200x = 70200
x = 70200/200
x = 351
OR
39 out of 200 picked chocolate chip
therefore, 39/200 = 0.195 = 19.5% ( 32.5% chose chocolate chip)
19.5% of 1800 = 0.195(1800) = 351 students
The simplified rational expression is (y - 3)/(y + 3). Where y ≠ -3.
<h3>How to simplify a rational expression?</h3>
A rational expression is in the p/q form. Where p and q are polynomial functions.
To simplify this rational equation,
- Factorize the polynomials in both numerator and denomiantor.
- Cancel out common factors if any.
- If the denominator and the numerator have no common factors except 1, then that is said to be the simplest form of the given rational expression.
<h3>Calculation:</h3>
The given rational equation is
![\frac{y^2 - 12y + 27 }{y^2 - 6y - 27}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E2%20-%2012y%20%2B%2027%20%7D%7By%5E2%20-%206y%20-%2027%7D)
Factorizing the expression in the numerator:
y² - 12y + 27 = y² - 9y - 3y + 27
⇒ y(y - 9) - 3(y - 9)
⇒ (y - 3)(y - 9)
Factorizing the expression in the denominator:
y² - 6y - 27 = y² - 9y + 3y - 27
⇒ y(y - 9) + 3(y - 9)
⇒ (y + 3)(y - 9)
Since they have (y - 9) as the common factor, we can simplify,
![\frac{y^2 - 12y + 27 }{y^2 - 6y - 27}=\frac{(y-3)(y-9)}{(y+3)(y-9)}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E2%20-%2012y%20%2B%2027%20%7D%7By%5E2%20-%206y%20-%2027%7D%3D%5Cfrac%7B%28y-3%29%28y-9%29%7D%7B%28y%2B3%29%28y-9%29%7D)
⇒ (y - 3)/(y + 3) where y ≠ -3(denomiantor)
Here there are no more common factors except 1; this is the simplest form of the given rational expression.
Learn more about simplifying rational expressions here:
brainly.com/question/1928496
#SPJ9